2020
DOI: 10.1109/access.2019.2963213
|View full text |Cite
|
Sign up to set email alerts
|

Automated Extraction of Human Settlement Patterns From Historical Topographic Map Series Using Weakly Supervised Convolutional Neural Networks

Abstract: Information extraction from historical maps represents a persistent challenge due to inferior graphical quality and the large data volume of digital map archives, which can hold thousands of digitized map sheets. Traditional map processing techniques typically rely on manually collected templates of the symbol of interest, and thus are not suitable for large-scale information extraction. In order to digitally preserve such large amounts of valuable retrospective geographic information, high levels of automatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 61 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…Uhl et al used USGS maps for human settlement footprint retrieval in their studies [3], [2]. By applying a weakly supervised CNN, they achieved promising results (i.e., recall of up to 0.96, F_measure of up to 0.79).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Uhl et al used USGS maps for human settlement footprint retrieval in their studies [3], [2]. By applying a weakly supervised CNN, they achieved promising results (i.e., recall of up to 0.96, F_measure of up to 0.79).…”
Section: Related Workmentioning
confidence: 99%
“…As far as the complexity is concerned, our model has 32.8M parameters. When we searched the literature for historical map processing, the training times and complexity of models are not generally reported but Uhl et al [2] reported that 138 million parameters used in their VGGNet-16 models. Our model has relatively lower number of parameters, training time and complexity because of the pretrained architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the accessible historical maps are digitally available only as scanned images; therefore, it is not possible to conduct quantitative and geometrical analysis from these maps without further processing [6]. However, multi-date historical maps or integrated usage of historical maps, aerial photographs, and satellite images can be used to extract ISPRS Int.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they explained the CNN architectures used in semantic segmentation such as U-Net, SegNet, and DeepLab. Moreover, deep learning-based methods have started to be implemented in historical map-related tasks recently [2,6,9,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation